Viktimisasi Terhadap Korban Penipuan Dengan Modus Penjualan Album K-POP - Kurniawaty, Yuli (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Fraud in selling K-Pop albums by unscrupulous business actors in Indonesia has caused the victimization of consumers who are K-pop fans. This condition is common among K-pop fans in Indonesia, but there are not many cases of fraud that end up being reported. Several fraud cases in Indonesia are used to analyze the factors that cause the victimization of consumers who are K-pop fans. Under the routine activity theory, it can be interpreted that the condition of the victim who is vulnerable and worthy as a victim has motivated the offender to commit fraud. In addition, the weak control and protection of victims also affect the victimization of victims.